Platypnea Orthodeoxia Syndrome Secondary to Intracardiac Shunt Following Orthotopic Liver Transplantation - Sophia R. Larson MD; Philip Vutien MD; Zachary L. Steinberg MD (Journal of Investigative Medicine High Impact Case Reports, 2020)
Platypnea orthodeoxia syndrome (POS) occurs when an upright position results in acute-onset hypoxemia and is relieved with recumbency. POS can be due to intracardiac shunting, intrapulmonary shunting, ventilation-perfusion mismatch, or a combination of these. We report a case of POS that developed 3 days post liver transplantation as a result of new-onset right to left shunting across a patent foramen ovale. Right heart catheterization revealed a posteriorly directed inferior vena cava likely due to altered inferior vena cava—right atrial junction anatomy as a result of liver transplantation. The patient underwent successful transcatheter patent foramen ovale closure with a 25-mm Gore Cardioform septal occluder device with immediate and sustained improvement in hypoxia.